Factors associated with mental health disorders in undergraduate students: A meta-analysis - Kartikasari, Dhian; Andarini, Sri; Wardhani, Viera; Windarwati, Heni D. (Narra J, 2025)
Mental health disorders are a significant issue, yet there is currently no consistent data regarding the factors that may contribute to their occurrence. The aim of this study was to identify the factors that may influence the occurrence of mental health disorders in the undergraduate student population. This meta-analysis, registered in PROSPERO, was conducted as of September 5, 2024. The systematic searches were conducted on three databases (Scopus, Embase, and PubMed). Data on factors related to the occurrence of mental health disorders in undergraduate students were collected to calculate pooled point estimates using the Mantel-Haenszel test. Out of 6,837 articles, 16 articles were included in the analysis. Our findings revealed that female students had a higher chance of experiencing mental health disorders compared to male students (OR: 1.43; 95%CI: 1.14–1.80; p-Egger of 0.1041; p-Heterogeneity of <0.0001; p=0.0020). The chance of having mental health disorders was also higher among single students compared to those in relationships (OR: 1.20; 95%CI: 1.02–1.43; p-Egger of 0.0535; p-Heterogeneity of 0.1130; p=0.0180). This study did not find any associations between age group, family income, smoking, living arrangements, years of study, or regularity of physical activity with the occurrence of mental health disorders. These findings could serve as a basis for improving policies aimed at reducing the rates of mental health disorders in undergraduate students.